THE MODERN CONCEPTS AND CONTAINS IN AGRO-MANAGER EDUCATION - Novkovic, Nebojsa; Somogyi, Sandor (Economics of Agriculture, 2006)
Economy system transition, process of privatization, and tendency of EU participation, indicate needs for the changing of present concept and contain in agro-manager education. Education is an important factor for economy development. Manager education in agro-business should be an important factor for the competitiveness increasing, at the local, and international market. Important question in education is a changing of concept, by using the modern theories, and solving the concrete (practical) problems. In the domain of concept of agro-manager education, it is necessary to extend their knowledge in the fields of multi-functional agriculture (agro-tourism, ecology, management of S.M.E., quality management, etc.). Three years study of agro-management should be adopted with needs of Farm management, or S.M.E. management, and four years study for the needs of corporative management, and Macro agro-management.